Bioactive Potential of Cydonia oblonga and Diospyros kaki Vinegars: Phenolic Content, Antioxidant and GST Inhibitory Activity, and Molecular Docking Studies. - Sahin, Zuhal; Sonmez, Fatih; Avci, Davut; Duran, Tulay; Darwich, Nourhane A.; Banerjee, Baisakhi (BioMed Research International, 2025)
Fruits and their peels are rich sources of bioactive compounds with significant health benefits. Vinegars produced from fruits and their peels are gaining increasing interest as a functional food due to their antioxidant, antimicrobial, and potential therapeutic properties. In this study, the four vinegars (Cydonia oblonga pulp vinegar [COV], Cydonia oblonga peel vinegar [COPV], Diospyros kaki pulp vinegar [DKV], and Diospyros kaki peel vinegar [DKPV]) were produced via natural fermentation. Total phenolic content (TPC), total flavonoid content (TFC), antioxidant properties (DPPH and ABTS activity), and glutathione S‐transferase (GST) inhibitory activity of these produced vinegars were evaluated. Additionally, in order to compare the properties of these products with natural home‐style/traditional, the same content and activities of Cydonia oblonga fruit vinegar (COFV) and Diospyros kaki fruit vinegar (DKFV) were examined. The results indicated that COPV exhibited the highest TPC (842.57 ± 56.79 mg GAE/L) and TFC (248.45 ± 55.08 mg catechin/L), while DKPV showed the highest GST inhibitory activity (81.25%). All samples demonstrated significant DPPH and ABTS radical scavenging potential. Vinegars derived from peels (COPV and DKPV) generally contain higher levels of bioactive compounds than the others. Additionally, docking results indicated that the carbonyl and hydroxyl groups and aromatic rings of main components in extracts interacted extensively with GST active cite via π‐donor, carbon and/or conventional H‐bonds, π‐anion, π‐alkyl, π‐π T‐shaped, and amide‐π stacked interactions. The findings suggest that peel vinegars are a promising source of natural antioxidants and potential GST inhibitors. These findings also highlight their potential value as functional food products.